Clinicoradiological profile and treatment outcomes in prostate cancer at a tertiary care cancer center in India - Astha Rajput; Shaik Maheboob Hussain; Neha Sonthwal; Gagan Gautam; Puneet Ahluwalia; Anirudh Punnakal; Harit Chaturvedi; Pankaj Dougall; Jaspriya Bal; Alok Gupta (Indian Journal of Medical and Paediatric Oncology)
Introduction: Prostate cancer is the most common solid cancer in men and is responsible for 11% of all cancer-related deaths. There are limited data available regarding clinicoradiological (prostate-specific membrane antigen [PSMA]-positron emission tomography [PET]/computed tomography [CT], magnetic resonance imaging, and bone scan) characteristics, treatment outcomes, and correlation of clinicoradiological characteristics with treatment outcomes of prostate cancer patients from India, especially in the era of PSMA-PET/CT scan. Methodology: This was a single center, retrospective, observational study, conducted for 6 months. We retrospectively collected the data of 332 prostate cancer patients treated between January 2015 and December 2017 at our institute. Results: Three hundred and thirty-two patients were enrolled and were divided into three groups depending on the stage and treatment modality, i.e., Group A, B, and C containing 205, 47, and 80 patients, respectively. The median age was 67 years, and the median prostate-specific antigen (PSA) was 19.3 ng/ml. Lower urinary tract symptoms (83.4%) and bone pain (8.1%) were the common presenting symptoms. PSMA-PET/CT scan revealed regional lymph node metastasis in 56.5% patients, bone metastasis in 35.7%, and visceral metastasis in 11.5% patients, respectively. In patients treated with curative intent, radical prostatectomy was performed in 61.74% of patients, whereas radiation therapy was performed in 47 (14.15%) patients. Among those treated with palliative intent, androgen deprivation therapy (ADT) alone (40) was the most preferred therapy followed by the combination of ADT with docetaxel (28) or abiraterone (12). Significantly (P = 0.006), a greater number of patients who were treated with ADT alone progressed to castration-resistant prostate cancer (CRPC) compared to those on combination ADT with either abiraterone or docetaxel. No significant difference was seen in the disease progression when treatment arm containing ADT with docetaxel was compared to ADT with abiraterone. Conclusion: Patients with metastatic disease had a higher median PSA level and also had a higher likelihood of having Gleason score 8–10. Among patients who were treated with palliative intent for metastatic disease, disease progression to CRPC state was significantly higher in those treated with ADT alone compared to those treated with either ADT + docetaxel or ADT + abiraterone.